Impacts of dietary humic acid supplementation on growth performance, some blood metabolites and carcass traits of broiler chicks - ARIF, MUHAMMAD; REHMAN, ABDUR; SAEED, MUHAMMAD; EL-HACK, MOHAMED EZZAT ABD; ARAIN, MUHAMMAD ASIF; HASEEBARSHAD, MUHAMMAD; ZAKRIA, HAFIZ MUHAMMAD; ABBASI, IMTIAZ HUSSAIN (The Indian Journal of Animal Sciences, 2016)
This study was designed to evaluate the effect of graded levels of humic acid (HA) supplementation on broiler performance. Day-old broiler chicks (300) were randomly divided into 5 groups under completely randomized design (CRD). Five iso-caloric and iso-nitrogenous broiler starter and finisher diets (HA0, HA1, HA2, HA3 and HA4) containing 0, 0.75, 1.5, 2.25 and 3 g/kg HA, respectively, were formulated and were randomly allotted to each group. Results indicated that, during starter phase highest weight gain (WG) was observed in chicks fed HA2 diet, but during finisher phase it was observed in birds fed HA3 diet. Weight gain during whole experiment was also highest in broiler fed HA3 diet. The best feed conversion ratio (FCR) was also observed in broiler fed HA3 diets. There were no influences of humic acid on carcass weight, liver weight, heart weight, gut length, breast weight, thigh weight and abdominal fat weight. Blood glucose, urea, Ca, P, creatinine, red blood cells, white blood cells and haemoglobin were not affected by humic acid supplementation but blood cholesterol and low density lipoprotein (LDL) level were significantly reduced (P<0.05) in HA3 and HA4 diets. Therefore, it could be concluded that humic acid as an organic feed additive could improve growth performance of broiler chicks and reduce levels of total and low density lipoprotein cholesterol in the blood. The best level of HA to be recommended is 2.25 g/kg diet.